Analysis of Patterns and Risk Factors for Malaria Incidence in Mimika Regency, Central Papua Indonesia in 2022-2025 - Fitra Wati; Sarliani (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2025)
Background: Malaria is an infectious disease that is still a public health problem in Indonesia, especially in the Papua region, including Mimika Regency. Malaria transmission is influenced by environmental, physical, biological, and behavioral factors of the community. Mimika Regency ranks first with the highest number of malaria cases in Indonesia, and various control efforts have been carried out but cases are still high. Objective: This study aims to analyze the patterns and risk factors of malaria incidence in Mimika Regency, Central Papua, in 2022–2025. Methods: This study used a quantitative descriptive approach with a correlational design. Data was collected through surveys and documentation of malaria cases in Nawaripi Village, Mimika Regency. The analysis was conducted to identify the relationship between environmental, behavioral, and malaria incidence factors. Results: The results show that the incidence of malaria in Mimika Regency is still very high, with an increasing trend of cases from year to year. Environmental factors such as poor sanitation, the presence of swamps, and waterlogging, as well as the behavior of people who do not use insecticide-treated mosquito nets and often do activities outside the house at night, contribute to the high incidence of malaria. Conclusion: The pattern of malaria incidence in Mimika Regency is influenced by a combination of environmental factors and community behavior. Control efforts need to be focused on improving the environment, educating healthy behaviors, and strengthening malaria prevention programs in a sustainable manner.